2012
DOI: 10.3109/08958378.2012.712165
|View full text |Cite
|
Sign up to set email alerts
|

Development of multi-route physiologically-based pharmacokinetic models for ethanol in the adult, pregnant, and neonatal rat

Abstract: Biofuel blends of 10% ethanol (EtOH) and gasoline are common in the USA, and higher EtOH concentrations are being considered (15-85%). Currently, no physiologically-based pharmacokinetic (PBPK) models are available to describe the kinetics of EtOH-based biofuels. PBPK models were developed to describe life-stage differences in the kinetics of EtOH alone in adult, pregnant, and neonatal rats for inhalation, oral, and intravenous routes of exposure, using data available in the open literature. Whereas ample data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…Review of the individual behaviors in this domain suggested increased responsiveness in high-dose males on PND 29, in response to both the click and tail-pinch stimuli. Although these individual endpoints did not reach statistical significance, the , ethanol is 6.7 kcal/g, and the retention rate of inhaled ethanol is 73% (Martin et al, 2012).…”
Section: Functional Observational Batterymentioning
confidence: 95%
See 2 more Smart Citations
“…Review of the individual behaviors in this domain suggested increased responsiveness in high-dose males on PND 29, in response to both the click and tail-pinch stimuli. Although these individual endpoints did not reach statistical significance, the , ethanol is 6.7 kcal/g, and the retention rate of inhaled ethanol is 73% (Martin et al, 2012).…”
Section: Functional Observational Batterymentioning
confidence: 95%
“…Further, studies reporting hyperactivity typically use oral ethanol doses of 4 g/kg/d or more during gestation. Oral doses between 3 and 6 g/kg yield peak BECs of 220-280 mg/dL in the dam during gestation (Abel, 1979;Church et al, 1990;Martin et al, 2012). For example, offspring of rats dosed by gavage with 5 g/kg ethanol from GD 8-20, which produced BECs of 270 mg/dL, were~50% more active than controls when tested Fig.…”
Section: Assessments Of Offspring: Unconditioned Behaviormentioning
confidence: 96%
See 1 more Smart Citation
“…It is instructive for the purpose of this study to examine these effects in relation to the ethanol content of the vapors (Table 1). Whereas tissue concentrations of the hydrocarbons comprising the gasoline mixtures are not available, blood ethanol concentrations (BECs) from these exposures can be estimated from the concentrations of ethanol in the air via available PBPK models (Martin et al, 2012;Martin et al, 2014). Given that the concentrations of ethanol in the vapor to which the rats were exposed were less than 7000 ppm (Table 1), calculated estimates of peak BEC do not exceed 5 mg/dL for any of the vapors tested .…”
Section: Ethanol Content As Predictor Of Effectmentioning
confidence: 99%
“…There are a number of PBPK models previously developed to describe the pharmacokinetics of ethanol in rodents and humans (Dumas-Campagna et al, 2014;Martin et al, 2012;Pastino and Conolly, 2000;Plawecki et al, 2008;Umulis et al, 2005), but currently no models describing ethyl acetate.…”
Section: Introductionmentioning
confidence: 99%